An Application of the Isolated Patellar Resurfacing (IPR) in the Treatment of Anterior Knee Pain in the Post-arthroplasty Patient - Yassin, Mustafa; Garti, Avraham; Weissbrot, Moshe; Ashkenazi, Uzi; Khatib, Muhammed; Robinson, Dror (Medical Science: Trends and Innovations Vol. 3, 2025)
Background: Total knee arthroplasty (TKA) has become the main surgical tool in the treatment of primary osteoarthritis of the knee. Outcomes appear to be similar both clinically and functionally, with or without patellar resurfacing. Purpose: Patellar resurfacing during prosthetic replacement of the knee is associated with loosening and the need for secondary revision. In many cases, the patella is left unreplaced during this procedure in order to decrease the revision risk. Some of these patients remain symptomatic after knee replacement. Secondary isolated resurfacing of the previously unresurfaced patella in total knee arthroplasty remains controversial. The aim of this retrospective study was to evaluate the outcome after isolated patellar resurfacing (IPR) as a second-stage procedure. Methods: The study included 33 patients (22 females/11 males) who underwent resurfacing of the patella with a mean follow-up of 44.8 ± 12.2 months. The mean age of the patients was 70.3 ± 15 (range 39–95) years at the time of operation. The average period between total knee arthroplasty and patellar resurfacing was 23.3 ± 15.2 months. The patient’s subjective satisfaction was assessed according to the Knee Society Score (KSS) questionnaire. Results: The mean objective KSS improved significantly from 41.6 ± 9 to 64.9 ± 11 (P < .01). The mean functional KSS also improved significantly from 41.6 ± 8 to 60.5 ± 9 (P < .01). Two patients (6%) needed further operative revision. Multivariate analysis indicates that results are better in males and in non-obese patients. Conclusions. Although clinical scores showed significant improvement, some patients have pain and remain dissatisfied following IPR. IPR should be considered in patients who underwent prosthetic knee bicompartmental. Patellar resurfacing should be considered if there is no evidence of prosthetic component malalignment and at least 12 months have passed since the primary implantation. Some patients are likely to suffer from AKP after knee arthroplasty. In persistent AKP, IPR should be performed provided there is no component malalignment per computerized tomography, no evidence of infection and preferably in a nonobese patient.